2018
DOI: 10.1186/s41702-017-0016-1
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate inhibits paclitaxel-induced apoptosis through the alteration of microRNA expression in human dermal papilla cells

Abstract: Background: Paclitaxel well known as anti-cancer drug has been shown to cause alopecia in chemotherapy. The paclitaxel chemotherapy-mediated alopecia is induced by apoptotic damage in human dermal papilla (HDP) cells. Epigallocatechin-3-gallate (EGCG) inhibits apoptosis against anti-cancer drug such as cisplatin. EGCG, one of the green tea extract ingredients, has been reported to enhance cell viability and to inhibit apoptosis. However, it is unclear that EGCG enhances cell viability and inhibits apoptosis ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Due to its high proliferative rate being similar to cancer cells, the hair follicle is an organ negatively affected by various chemotherapies [53]. Most of the recommended anticancer drugs for lung cancer significantly induced apoptosis in dermal papilla cells consequently causing drug induced-alopecia and low quality of life in cancer patients [38][39][40]. The absence of apoptosis in human dermal papilla DPCs cells treated with colicin N strongly supports the development of colicin N as a selective anticancer drug for treatment of lung cancer.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Due to its high proliferative rate being similar to cancer cells, the hair follicle is an organ negatively affected by various chemotherapies [53]. Most of the recommended anticancer drugs for lung cancer significantly induced apoptosis in dermal papilla cells consequently causing drug induced-alopecia and low quality of life in cancer patients [38][39][40]. The absence of apoptosis in human dermal papilla DPCs cells treated with colicin N strongly supports the development of colicin N as a selective anticancer drug for treatment of lung cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Hair loss is one of major side effects that lessen quality of life in lung cancer patients administered with current standard chemotherapy [35][36][37]. Apoptosis in dermal papilla cells caused by anticancer drugs leads to chemotherapy-induced alopecia [38][39][40]. Therefore, the toxic profile of colicin N in normal cells was investigated in human dermal papilla DPCs cells.…”
Section: Selective Apoptosis-inducing Effect Of Colicin N In Various Human Lung Cancer Cellsmentioning
confidence: 99%
“…Inducing cell death in dermal papilla cells coincides with a common side effect of current chemotherapeutic drugs, namely hair loss, which can cause psychological distress in lung cancer patients [40] , [41] , [42] , [43] , the safety profiles of ColN WT and ColN +12 were evaluated in human dermal papilla DPCs cells. The cultures were treated with 0–10 μM of ColN WT and ColN +12 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, EGCG is used for the treatment of hair loss as a reductase inhibitor [109]. Cellular studies have shown that EGCG increases cell proliferation and decreases cell death by altering the miRNA profiles in HDP cells and sequentially affects paclitaxel-mediated hair loss [112]. In vitro experiments indicated that EGCG promotes hair growth by upregulating phosphorylated Erk and Akt and by increasing the Bcl-2/Bax ratio [108].…”
Section: Natural Products For Hair Regrowthmentioning
confidence: 99%